ChemInform Abstract: Chemistry and Biology of Microsomal Prostaglandin E2 Synthase‐1 (mPGES‐1) Inhibitors as Novel Antiinflammatory Agents: Recent Developments and Current Status. Issue 21 (6th May 2016) - Khurana, Puneet; Jachak, Sanjay M.
Abstract: Review: 130 refs.